2017
DOI: 10.1002/cptx.19
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Phenotyping for Autism Spectrum Disorders in Mice

Abstract: Autism spectrum disorder (ASD) represents a heterogeneous group of disorders characterized by alterations in three behavioral symptom domains: social interactions, verbal and nonverbal communication, and repetitive behaviors. Increasing prevalence of ASD in recent years suggests that exposure to environmental toxicants may be critical in modulating etiology of this disease. As clinical diagnosis of autism still relies on behavioral evaluation, it is important to be able to assess similar behavioral traits in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 68 publications
(152 reference statements)
4
58
0
4
Order By: Relevance
“…We tested mice for 5 min with a 5 min baseline in an open-field apparatus (43 cm × 43 cm × 33 cm) while videotaping, and investigators blinded to experimental conditions scored eight different commonly observed behaviors including anogenital sniffing (ag), nose-to-nose (n2n), anogenital sniffing while following the stimulus mouse (ag/follow), following (follow), orienting to the stimulus mouse (orient), approaching the stimulus mouse (approach), investigation of the stimulus mouse (investigation), and being investigated by the stimulus mouse (investigated by stim), adapted from refs. 42,43 . Rare behaviors, such as being chased or chasing, grooming, or side-by-side huddling were also scored but then were excluded due to very low frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…We tested mice for 5 min with a 5 min baseline in an open-field apparatus (43 cm × 43 cm × 33 cm) while videotaping, and investigators blinded to experimental conditions scored eight different commonly observed behaviors including anogenital sniffing (ag), nose-to-nose (n2n), anogenital sniffing while following the stimulus mouse (ag/follow), following (follow), orienting to the stimulus mouse (orient), approaching the stimulus mouse (approach), investigation of the stimulus mouse (investigation), and being investigated by the stimulus mouse (investigated by stim), adapted from refs. 42,43 . Rare behaviors, such as being chased or chasing, grooming, or side-by-side huddling were also scored but then were excluded due to very low frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in repetitive behavior and anxiety levels were evaluated through the marble burying test in line with previously described methods . The trials were recorded using a Sony Cyber‐shot DSC‐W800 20.1 MP camera.…”
Section: Methodsmentioning
confidence: 99%
“…The three‐chamber test was used to measure sociability as previously described . The sociability apparatus (60 cm L × 45 cm W × 26 cm H) was made from clear acrylic walls and divided into three chambers equal in area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations